Dietary intake and dinner timing among shift workers in Japan. Issue 6 (27th November 2018) - Nakamura, Mieko; Miura, Ayako; Nagahata, Tomomi; Toki, Atsushi; Shibata, Yosuke; Okada, Eisaku; Ojima, Toshiyuki
Abstract : Objectives: Shift workers are at an increased risk of diet‐related chronic conditions. We aimed to investigate dietary intake and dinner timing among shift workers. Methods: A questionnaire survey was administered to the employees of 43 companies in Japan between December 2013 and February 2014. The dietary intake of workers was assessed through a validated food frequency questionnaire (FFQ) . Nutrient intake was evaluated by adjusting the total energy intake using a nutrient residual model. Analysis of covariance was used to obtain the means of total energy and nutrient intake by the work schedule (shift or daytime), and the means of total energy and nutrient intake by dinner timing (regular or irregular) . Results: Valid responses were obtained from 2, 062 daytime and 302 shift workers. A valid response rate to the FFQ was slightly but significantly lower among shift workers than among daytime workers (87.1% and 91.8 %). When compared to daytime workers, shift workers were more likely to eat dinner at irregular times (46.7% vs. 3.6%). Shift work was associated with a higher mean body mass index (23.4 kg/m 2 vs. 22.3 kg/m 2 ), a higher proportion of being overweight (27.7% and 18.8%), higher total energy intake, and lower intakes of dietary fiber, vitamin B2, folic acid, vitamin C, potassium, calcium, magnesium and iron. Moreover, irregular dinner timing was associated with lower intakes of protein, folic acid, and zinc in daytime workers, and lower intakes of carbohydrate and copper in shift workers. Conclusions: These findings indicate a need to improve the diet of shift workers.